CRZ1 regulator and calcium cooperatively modulate holocellulases gene expression in Trichoderma reesei QM6a - Martins-Santana,Leonardo (2020)
Abstract Trichoderma reesei is the main filamentous fungus used in industry to produce cellulases. Here we investigated the role of CRZ1 and Ca2+signaling in the fungus T. reesei QM6a concerning holocellulases production. For this, we first searched for potential CRZ1 binding sites in promoter regions of key genes coding holocellulases, as well as transcriptional regulators and sugar and calcium transporters. Using a nearly constructed T. reeseiAcrz1 strain, we demonstrated that most of the genes expected to be regulated by CRZ1 were affected in the mutant strain induced with sugarcane bagasse (SCB) and cellulose. In particular, our data demonstrate that Ca2+ acts synergistically with CRZ1 to modulate gene expression, but also exerts CRZ1-independent regulatory role in gene expression in T. reesei, highlighting the role of the major regulator Ca2+ on the signaling for holocellulases transcriptional control in the most part of cellulases genes here investigated. This work presents new evidence on the regulatory role of CRZ1 and Ca2+ sensing in the regulation of cellulolytic enzymes in T. reesei, evidencing significant and previously unknown function of this Ca2+sensing system in the control key transcriptional regulators (XYR1 and CRE1) and on the expression of genes related to sugar and Ca2+ transport.